THE RELATIONSHIP OF FAMILY SUPPORT TO THE PREVENTION OF HYPERTENSION COMPLICATIONS IN THE ELDERLY - Maya Cobalt Angio Septianingtyas; Siti Juwariyah; Danny Putri Sulityaningrum (Indonesian Journal of Community Health Nursing, 2024)
ABSTRACT Introduction: Hypertension is a health problem that most often occurs in the elderly, because the elderly will experience a decrease in physiological function due to degenerative processes, one of the diseases of the cardiovascular system that most often occurs in the elderly due to aging and the cumulative impact of the lifestyle of the elderly in their youth. Hypertension in the elderly has the potential for complications such as coronary heart disease and kidney failure, so it requires routine treatment and several routine precautions that can prevent hypertension complications and support from the family is very influential. Methodology: This study aims to analyze the relationship between family support and the prevention of hypertension complications in the elderly. This research is a correlational descriptive study using a cross sectional design with a quantitative approach. The sample was selected using accidental sampling technique with a total sample of 68 respondents. Statistical tests use the Spearman rho test. Results: The results of the study show that there is a relationship between family support and the prevention of hypertension complications in the elderly with a positive correlation and very strong strength (p value = <0.001; r= 0.859). Conclusion: there is a relationship between family support and the prevention of hypertension complications in the elderly. The recommendation from the results of this research is the importance of family support in preventing hypertension complications in elderly people with hypertension so that they are more confident and obedient in preventing hypertension complications. Keywords: Hypertension, prevention of hypertension complications, family support, elderly